Corporate control, tax practices, and gender diversity: Evidence from France - LADHARI, Habiba (International journal of economic perspectives, 2025)
This study investigates the relationship between ownership concentration and corporate tax avoidance using a panel of 242 French listed firms from 2009 to 2022. Employing Prais–Winsten regression, we find that firms with concentrated ownership display a significantly higher propensity for tax avoidance, consistent with the entrenchment perspective of agency theory. Controlling shareholders appear to exploit their dominant position to pursue aggressive tax strategies that enhance private benefits, often to the detriment of minority stakeholders an effect amplified in the French institutional environment characterized by weak investor protections and highly concentrated ownership structures. Building on Social Identity Theory, we further examine the moderating role of board gender diversity. Our results reveal that gender-diverse boards act as a critical counterbalance to the opportunistic tax behaviors associated with controlling shareholders. Gender-diverse boards significantly weaken the positive association between ownership concentration and tax avoidance.These findings carry important implications for regulators, policymakers, and corporate governance practitioners. Strengthening investor protections and encouraging board gender diversity may serve as effective governance mechanisms to curb entrenched behaviors and reduce aggressive tax strategies.